Oncomarkers as a factor of risk in the regions with bad ecological situation - T. V. Solomatina; L. V. Kapilevich (Бюллетень сибирской медицины)
By immune-enzyme analysis the content of oncomarkers in serum of blood that exist in people living in the territories of the Tomsk region with bad ecological situation was researched. It was established that practically all people living in the polluted territories have deflections from normal conditions of oncomarkers, but in the control-less than 70%. The deflections on 2 or more oncomarkers in control exist in less than 10% researched people, and in the researched regions-more than 40%.